CHSLD, Mon Amour (version longue) (2021)
This is "CHSLD, Mon Amour (version longue)" by Danic Champoux on Vimeo, the home for high quality videos and the people who love them.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; canada; care; cinéma; communication; corps; cours; discipline; documentaire; montréal; premier cycle; périodes historiques; québev; ressource en ligne; régions géographiques; santé; sex1920; soin; thématiques